Batu Batikam dan Batu Baliyang Monumen Resolusi Konflik Minangkabau - Inoki Ulma Tiara (Journal on Education, 2023)
Batu Batikam and Batu Bali which are conflict resolution or peace monuments in Minangkabau between Datuak Katamanggungan developing his Laras Koto Piliang with Datuak Parpatiah Nan Sabatang who trusts his Laras Bodi Caniago. Before peace is reached there is conflict or dispute caused by different perspectives in running the government. Koto Piliang with his aristocratic principles while Bodi Caniago wants consensus to emerge from under tasbasuik from the earth. Differences in perspectives turned into open conflict without violence due to the division of areas that were not in accordance with the initial agreement. So Batu Batikam and Batu Bali were stabbed with a dagger and a stick to show supernatural powers, release anger, and as a vow of peace and complement each other as brothers.